Performa 09. Back to Futurism. - Goldberg, Roselee; Sandler, Irving (New York : Performa Publications, 2009)
Rubell, Jennifer ; Ben-Er, Guy ; Fast, Omer ; Breitz, Candice ; Chessa, Luciano ; Mutu, Wangechi ; Kelley, Mike ; Gonzalez-Foerster, Dominique ; Fischerspooner ; Sherman, Stuart ; Balula, Davide ; DeNike, Jen ; Woolfalk, saya ; Greaud, Loris ; Coates, Emily ; Mroué, Rabih ; Désanges, Guillaume ; Lutker, Shana ; Jonas, Joan ; Gaillard, Cyprien ; Cytter, Keren ; van der Werve, Guido ; Sacks, Ruth ; Amir, Einat ; Hassabi, Maria ; Bassanini, Katia ; Kirk, Lisa ; Miksys, Darius ; Framis, Alicia ; Ueda, Mai ; Lin, Tan ; Eros, Bradley
boek